OMG... we're in a horror movie! - Bandele, Ajala; Hatfield, Tom (Screenwriter); McGowan, Brendan (Actor); Wang, Sharon Mae (Alchemical Brothers, 2016)
Six friends having a weekly board game night are interrupted by a booming movie trailer voice from the sky. Inexplicably, they find themselves trapped in a Horror Movie. Who amongst them will turn into a homicidal killer? Who will be the sole survivor? And who will be the first to die in the shower? Struggling to break free from the stereotypes that would see them dead, each of the friends try to stay alive in whatever hopelessly desperate ways they can.